The multilateral GATT negotiations - Wedige Dewitz (Intereconomics, 1979)
The final package of the seventh round of multilateral GATT negotiations has been ready for initialling since April 11, 1979. What has been achieved in these negotiations, commonly known as the Tokyo Round, and what has been left undone?
Keywords: 330; World Trade